Bridging Culture, Islamic Values, and Mathematics: Learning Geometry Concepts through the Great Mosque of Madaniyah Karanganyar - Hery Nugroho; Sugiman Sugiman (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2026)
Ethnomathematical studies in Indonesia have widely explored the presence of geometric concepts embedded in Muslim worship buildings, particularly mosques. These studies highlight how architectural structures and ornamental patterns reflect mathematical ideas rooted in cultural practices. Therefore, the research aims to explore and explain the geometric concepts in the buildings and ornaments of the Great Mosque of Madaniyah Karanganyar. This research employ ethnography as an approach to answer four main questions, namely